Integrating ESG Principles and Responsible Artificial Intelligence Governance: A Sustainable Transformation Framework for Turbulent Markets - Tanner, Leopold (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This paper proposes an integrated framework combining environmental, social, and governance (ESG) principles with responsible artificial intelligence (AI) governance to enhance organizational resilience in turbulent markets. Using a mixed-methods design, the study evaluates the relationship between sustainability-oriented strategies and technological governance through empirical analysis of ESG and AI maturity indices. A key finding conceptualizes systemic instability as a function of financial leverage L and AI-driven gradients GAI, where economic pressure E = k ⋅ L ⋅ GAI. The results indicate that firms adopting integrated ESG-AI strategies exhibit significantly higher resilience and stakeholder trust compared to those relying on fragmented compliance approaches. Finally, the proposed framework is structured around four pillars: strategic alignment, responsible AI mechanisms, dynamic risk assessment, and stakeholder-oriented performance measurement. This contribution advances the understanding of sustainable transformation, arguing that ESG and AI are mutually reinforcing drivers of long-term value creation.